Pertumbuhan Padi Gogo yang dipengaruhi oleh Aplikasi Pupuk Hayati dan Pupuk NPK pada Andisols - Betty Natalie Fitriatin; Robi Natalie Silpanus; Tien Natalie Turmuktini; Emma Trinurani Sofyan; Anni Natalie Yuniarti (Soilrens, 2018)
ABSTRACT Intensive inorganic may lead to land degradation, and can be amended with the aid of biofertilizers . This study was conducted to investigate the application of biofertilizer (phosphatesolubilizing mircrobes and nitrogen-fixing bacteria) and inorganic fertilizers on the growth of upland rice on Andisols. Randomized Block Design (RBD) in factorial pattern were used as experimental design, which consisted of  two factors with three replications. The first factor consisted of biofertilizer addition dosages: without biofertilizer, biofertilizer consortia 1 (Pseudomonas mallei, P. cepaceae, Aspergillus niger and Penicillium sp., Azotobacter  chroococum, Azospirillum sp.), biofertilizer consortia 2 (Azotobacter choroococum, A. viilandii, Azospirillum, Pseudomonas cepaceae, Penicillium and Acitenobacter) and the mixture of biofertizer consortia 1 and 2. The second factor were Nitrogen-Phosphate-Potassium fertilizer which consisted of four levels (100%, 75%, 50% and 25% of The Indonesian Ministry of Agriculture recommended dosage). The results showed that the application of  biofertilizer consortia increased the growth of upland rice and fertilizer efficiency on Andisols.  Keywords : Andisols, biofertilizers, NPK fertilizers, upland rice